2010
DOI: 10.1016/j.cellsig.2009.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Prenylation-deficient G protein gamma subunits disrupt GPCR signaling in the zebrafish

Abstract: Prenylation of G protein gamma (γ) subunits is necessary for the membrane localization of heterotrimeric G proteins and for functional heterotrimeric G protein coupled receptor (GPCR) signaling. To evaluate GPCR signaling pathways during development, we injected zebrafish embryos with mRNAs encoding Gγ subunits mutated so that they can no longer be prenylated. Low-level expression of these prenylation-deficient Gγ subunits driven either ubiquitously or specifically in the primordial germ cells (PGCs) disrupts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 99 publications
1
20
0
Order By: Relevance
“…As in D. melanogaster, the isoprenoid branch of the pathway seems to be required, as inhibiting either Hmgcr or geranylgeranyl transferase disrupts PGC migration. Recent data suggest a role for the Hmgcr pathway in the geranylation of the Gγ subunits required directly for GPCR signalling in zebrafish PGCs 83 . Additional experiments are required to determine whether geranylation also affects the guidance of germ cells by the soma similar to D. melanogaster .…”
Section: Migratory Paths Of Pgcsmentioning
confidence: 99%
“…As in D. melanogaster, the isoprenoid branch of the pathway seems to be required, as inhibiting either Hmgcr or geranylgeranyl transferase disrupts PGC migration. Recent data suggest a role for the Hmgcr pathway in the geranylation of the Gγ subunits required directly for GPCR signalling in zebrafish PGCs 83 . Additional experiments are required to determine whether geranylation also affects the guidance of germ cells by the soma similar to D. melanogaster .…”
Section: Migratory Paths Of Pgcsmentioning
confidence: 99%
“…By sequestering free G, this protein blocks the activation of its downstream effectors (Federman et al, 1992). Additionally, we expressed a mutant G2 (G2C68S), which was recently shown to interfere with the membrane localization of G and its function in PGCs (Mulligan et al, 2010). Whereas control PGCs expressing GFP were clustered in the region of the presumptive gonad at 24 hpf (Fig.…”
Section: Inhibition Of G Signaling Interferes With Pgc Migrationmentioning
confidence: 99%
“…It has been shown that prenylation of G protein gamma subunits is necessary to facilitate directed migration of primordial germ cells (PGC) (Mulligan et al, 2010; Mulligan and Farber, 2011). The parapineal organ also migrates directionally.…”
Section: Discussionmentioning
confidence: 99%